Tear-resistant antibacterial nonwoven fabric and preparation method thereof
Through the combination of modified silica-silicon protein composite solution and modified nanocopper sol with polypropylene and succinyl polysan, the problems of poor antibacterial and tear resistance of nonwovens are solved, and the nonwovens are significantly improved performance.
Patent Information
- Application Number
- CN202310014061.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-05
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-01-05
AI Technical Summary
There are problems in the preparation of nonwoven fabrics with poor antibacterial properties and poor tear resistance.
The modified silica-silicon protein composite solution and modified nanocopper sol were mixed with polypropylene and succinyl polysan to prepare non-woven fabrics by meltblown spinning, and impregnate and roll in antibacterial finishing solution to enhance Antibacterial and tear resistance of nonwoven fabrics.
The antibacterial and tear resistance of non-woven fabrics is significantly improved, ensuring its effectiveness in application.
Smart Images

Figure BDA0004038734300000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of non-woven fabric manufacturing, in particular to a tear-resistant and antibacterial non-woven fabric and a preparation method thereof. Background Art
[0002] Non-woven fabrics, also known as nonwoven fabrics, are not made of yarns interwoven and knitted together one by one. Non-woven fabrics have broken through the traditional textile principles and have the advantages of short process flow, fast production rate, low cost, high output and wide application. Non-woven fabrics are breathable, have excellent filtering performance, do not produce fiber debris, have high filtering efficiency and durability, and feel similar to cotton, but are easier to form than cotton fabrics and are cheaper. Non-woven fabrics are colorful, lightweight, environmentally friendly, recyclable, and are widely used in medical, clothing, industry, and agriculture. However, the current non-woven fabrics are easy to prepare and still have problems with poor antibacterial properties and poor tear resistance.
[0003] In order to solve the above problems, the present invention provides a tear-resistant and antibacterial non-woven fabric and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a tear-resistant antibacterial non-woven fabric and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a tear-resistant antibacterial nonwoven fabric, characterized in that it comprises the following steps:
[0007] Step 1: taking a modified silica-silk fibroin composite solution, a modified nano copper sol, and deionized water, and mixing them evenly to obtain an antibacterial finishing solution;
[0008] Step 2: Evenly mix polypropylene and succinoglycan, dry, melt-blown and roll to obtain a non-woven fabric;
[0009] Step 3: Take the non-woven fabric, soak it in deionized water for 30-40 minutes, wash it, and dry it; take the non-woven fabric and immerse it in the antibacterial finishing liquid at 25-35°C for 20-25 minutes, roll it, and dry it at 70-75°C to obtain a tear-resistant antibacterial non-woven fabric.
[0010] More optimally, in step one, the preparation method of the modified silica-silk fibroin composite solution is: take silica gel, heat to 45-50°C, add polyhexamethylene guanidine, continue stirring for 3-5h, add silk fibroin and ethylenediaminetetraacetic acid, stir at 25-30°C for 70-80min, ultrasonicate for 70-80min, and dry to obtain a modified silica-silk fibroin composite solution.
[0011] More optimally, the preparation method of the silica gel is: take anhydrous ethanol and ethyl orthosilicate, stir for 18-20 minutes at 25-28°C, add ammonia water, stir for 2-3 hours, adjust the pH value of the solution to 5-5.5 with hydrochloric acid, add tannic acid, continue stirring for 2-3 hours, add concentrated ammonia water, adjust the pH value to 8-8.5, age for 11-12 hours, and obtain silica gel.
[0012] More optimally, in step one, the preparation method of the modified nano copper sol is: take potassium borohydride and deionized water, stir evenly to obtain a potassium borohydride solution; take copper sulfate, add deionized water to obtain a copper sulfate solution, add sodium dodecyl sulfate, polyvinyl pyrrolidone, and ethylenediamine, stir for 1-2 hours, heat to 42-45°C, continue stirring, add potassium borohydride solution, and continue stirring for 3-5 minutes to obtain a modified nano copper sol.
[0013] More optimally, in step 1, the mass ratio of the modified silica-silk fibroin composite solution, the modified nano-copper sol, and deionized water is 25:(2-3):(10-12).
[0014] More optimally, the nonwoven fabric comprises the following components: 60-70 parts of polypropylene and 8-12 parts of succinoglycan by weight.
[0015] More optimally, in step 2, polypropylene and succinoglycan are mixed evenly, dried at 75-80°C for 1-2h, melt-blown at 240-260°C, and wound at a winding speed of (5-10) m / min to obtain a non-woven fabric.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0017] (1) The present invention uses polypropylene and succinoglycan to prepare a polypropylene non-woven fabric, and then immerses the non-woven fabric in an antibacterial finishing liquid and presses it to obtain a tear-resistant antibacterial non-woven fabric.
[0018] The present invention adds silica gel to the antibacterial finishing liquid, uses tannic acid to prepare the silica gel, increases the specific surface area of silica, greatly increases its active sites, and enables more polyhexamethylene guanidine with antibacterial properties to be grafted on the surface of silica, thereby enhancing the antibacterial effect of the finishing liquid. Then, silk fibroin is added to further modify the silica, thereby enhancing the tear resistance of the non-woven fabric.
[0019] The present invention uses ethylenediamine to modify nano copper particles, grafting amino groups on nano copper, and the amino groups can react with the silanol groups on silicon dioxide to enhance the dispersibility of nano copper in the finishing solution and improve the antibacterial effect of the non-woven fabric. At the same time, nano copper can chelate with ethylenediaminetetraacetic acid in the modified silicon dioxide-silk fibroin composite solution to enhance the stability of nano copper and the antibacterial effect of the non-woven fabric.
[0020] By controlling the mass ratio of modified silica-silk fibroin composite solution, modified nano-copper sol and deionized water to 25:(2-3):(10-12), the antibacterial effect of the non-woven fabric reaches the best state. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The chemical reagents used in the present invention are purchased from the following sources:
[0023] Polypropylene, Z30S, was purchased from Sinopec Xinjiang Dushanzi Petrochemical Co., Ltd.;
[0024] Tetraethyl orthosilicate was purchased from Xilong Science Co., Ltd.
[0025] Example 1
[0026] Step 1: Preparation of modified silica-silk fibroin composite solution:
[0027] Take 100 mL of anhydrous ethanol and 34 mL of ethyl orthosilicate, stir at 27 ° C for 19 minutes, add 36 mL of ammonia water, stir for 2.5 hours, adjust the pH value of the solution to 5.5 with 0.1 mol / L hydrochloric acid, add 1 g of tannic acid, continue stirring for 2.5 hours, add 28% concentrated ammonia water, adjust the pH value to 8, and age for 11.5 hours to obtain silica gel;
[0028] Take 8 g of silica gel, heat it to 47°C, add 0.7 g of polyhexamethylene guanidine, continue stirring for 4 h, add 6 g of silk fibroin and 2 g of ethylenediaminetetraacetic acid, stir at 28°C for 75 min, ultrasonicate for 75 min, and dry to obtain a modified silica-silk fibroin composite solution.
[0029] Step 2: Preparation of modified nano copper sol:
[0030] Take 0.16g of potassium borohydride and 20ml of deionized water, stir evenly to obtain a potassium borohydride solution; take 0.6g of copper sulfate, add 50mL of deionized water to obtain a copper sulfate solution, add 1.5g of sodium dodecyl sulfate, 2.5g of polyvinyl pyrrolidone, and 2mL of ethylenediamine, stir for 1.5h, heat to 43°C, continue stirring, add potassium borohydride solution, at this time the solution changes from light blue to reddish brown, continue stirring for 4min to obtain a modified nano-copper sol.
[0031] Step 3: Preparation of antibacterial finishing liquid:
[0032] Take 50 g of modified silica-silk fibroin composite solution, 5 g of modified nano copper sol, and 22 g of deionized water, mix them evenly, and obtain an antibacterial finishing solution.
[0033] The mass ratio of modified silica-silk fibroin composite solution, modified nano-copper sol and deionized water is 25:2.5:11.
[0034] Step 4: Preparation of non-woven fabric:
[0035] 65 parts of polypropylene and 10 parts of succinoglycan were mixed evenly, dried at 77°C for 1.5 hours, melt-blown at 250°C, with a winding speed of 5 m / min and a receiving distance of the melt-blown fabric of 300 mm to obtain a non-woven fabric;
[0036] Take the non-woven fabric, soak it in deionized water for 35 minutes, wash it, and dry it; take the non-woven fabric and immerse it in antibacterial finishing liquid at 30°C for 23 minutes, roll it on a vertical rolling mill, and dry it at 72°C to obtain a tear-resistant antibacterial non-woven fabric.
[0037] Example 2
[0038] Step 1: Preparation of modified silica-silk fibroin composite solution:
[0039] Take 100 mL of anhydrous ethanol and 34 mL of ethyl orthosilicate, stir at 25°C for 18 min, add 36 mL of aqueous ammonia, stir for 2 h, adjust the pH value of the solution to 5 with 0.1 mol / L hydrochloric acid, add 1 g of tannic acid, continue stirring for 2 h, add 28% concentrated aqueous ammonia, adjust the pH value to 8, and age for 11 h to obtain silica gel;
[0040] Take 8 g of silica gel, heat it to 45°C, add 0.7 g of polyhexamethylene guanidine, continue stirring for 3 h, add 6 g of silk fibroin and 2 g of ethylenediaminetetraacetic acid, stir at 25°C for 70 min, ultrasonicate for 70 min, and dry to obtain a modified silica-silk fibroin composite solution.
[0041] Step 2: Preparation of modified nano copper sol:
[0042] Take 0.16g of potassium borohydride and 20ml of deionized water, stir evenly to obtain a potassium borohydride solution; take 0.6g of copper sulfate, add 50mL of deionized water to obtain a copper sulfate solution, add 1.5g of sodium dodecyl sulfate, 2.5g of polyvinyl pyrrolidone, and 2mL of ethylenediamine, stir for 1h, heat to 42°C, continue stirring, add potassium borohydride solution, at this time the solution changes from light blue to reddish brown, continue stirring for 3min to obtain a modified nano-copper sol.
[0043] Step 3: Preparation of antibacterial finishing liquid:
[0044] Take 50 g of modified silica-silk fibroin composite solution, 4 g of modified nano copper sol, and 20 g of deionized water, mix them evenly, and obtain an antibacterial finishing solution.
[0045] The mass ratio of modified silica-silk fibroin composite solution, modified nano-copper sol and deionized water is 25:2:10.
[0046] Step 4: Preparation of non-woven fabric:
[0047] 60 parts of polypropylene and 8 parts of succinoglycan were mixed evenly, dried at 75°C for 1 hour, melt-blown at 240°C, with a winding speed of 5 m / min and a receiving distance of the melt-blown fabric of 300 mm to obtain a non-woven fabric;
[0048] Take the non-woven fabric, soak it in deionized water for 30 minutes, wash it, and dry it; take the non-woven fabric and immerse it in antibacterial finishing liquid at 25°C for 20 minutes, roll it on a vertical rolling mill, and dry it at 70°C to obtain a tear-resistant antibacterial non-woven fabric.
[0049] Example 3
[0050] Step 1: Preparation of modified silica-silk fibroin composite solution:
[0051] Take 100 mL of anhydrous ethanol and 34 mL of ethyl orthosilicate, stir at 28°C for 20 min, add 36 mL of aqueous ammonia, stir for 3 h, adjust the pH value of the solution to 5.5 with 0.1 mol / L hydrochloric acid, add 1 g of tannic acid, continue stirring for 3 h, add 28% concentrated aqueous ammonia, adjust the pH value to 8.5, age for 12 h, and obtain silica gel;
[0052] Take 8 g of silica gel, heat it to 50°C, add 0.7 g of polyhexamethylene guanidine, continue stirring for 5 h, add 6 g of silk fibroin and 2 g of ethylenediaminetetraacetic acid, stir at 30°C for 80 min, ultrasonicate for 80 min, and dry to obtain a modified silica-silk fibroin composite solution.
[0053] Step 2: Preparation of modified nano copper sol:
[0054] Take 0.16g of potassium borohydride and 20ml of deionized water, stir evenly to obtain a potassium borohydride solution; take 0.6g of copper sulfate, add 50mL of deionized water to obtain a copper sulfate solution, add 1.5g of sodium dodecyl sulfate, 2.5g of polyvinyl pyrrolidone, and 2mL of ethylenediamine, stir for 2h, heat to 45°C, continue stirring, add potassium borohydride solution, at this time the solution changes from light blue to reddish brown, continue stirring for 5min to obtain a modified nano-copper sol.
[0055] Step 3: Preparation of antibacterial finishing liquid:
[0056] Take 50 g of modified silica-silk fibroin composite solution, 6 g of modified nano copper sol, and 24 g of deionized water, mix them evenly, and obtain an antibacterial finishing solution.
[0057] The mass ratio of modified silica-silk fibroin composite solution, modified nano-copper sol and deionized water is 25:3:12.
[0058] Step 4: Preparation of non-woven fabric:
[0059] 70 parts of polypropylene and 12 parts of succinoglycan were mixed evenly, dried at 80°C for 2h, melt-blown at 260°C, with a winding speed of 5m / min and a receiving distance of the melt-blown fabric of 300mm to obtain a non-woven fabric;
[0060] Take the non-woven fabric, soak it in deionized water for 40 minutes, wash it, and dry it; take the non-woven fabric and immerse it in antibacterial finishing liquid at 35°C for 25 minutes, roll it on a vertical rolling mill, and dry it at 75°C to obtain a tear-resistant antibacterial non-woven fabric.
[0061] Example 4: No ethylenediaminetetraacetic acid is added to modify the silicon dioxide, and the rest is the same as Example 1.
[0062] Step 1: Preparation of modified silica-silk fibroin composite solution:
[0063] Take 100 mL of anhydrous ethanol and 34 mL of ethyl orthosilicate, stir at 27 ° C for 19 minutes, add 36 mL of ammonia water, stir for 2.5 hours, adjust the pH value of the solution to 5.5 with 0.1 mol / L hydrochloric acid, add 1 g of tannic acid, continue stirring for 2.5 hours, add 28% concentrated ammonia water, adjust the pH value to 8, and age for 11.5 hours to obtain silica gel;
[0064] Take 8 g of silica gel, heat it to 47°C, add 0.7 g of polyhexamethylene guanidine, continue stirring for 4 h, add 6 g of silk fibroin, stir at 28°C for 75 min, ultrasonicate for 75 min, and dry to obtain a modified silica-silk fibroin composite solution.
[0065] Step 2: Preparation of modified nano copper sol:
[0066] Take 0.16g of potassium borohydride and 20ml of deionized water, stir evenly to obtain a potassium borohydride solution; take 0.6g of copper sulfate, add 50mL of deionized water to obtain a copper sulfate solution, add 1.5g of sodium dodecyl sulfate, 2.5g of polyvinyl pyrrolidone, and 2mL of ethylenediamine, stir for 1.5h, heat to 43°C, continue stirring, add potassium borohydride solution, at this time the solution changes from light blue to reddish brown, continue stirring for 4min to obtain a modified nano-copper sol.
[0067] Step 3: Preparation of antibacterial finishing liquid:
[0068] Take 50 g of modified silica-silk fibroin composite solution, 5 g of modified nano copper sol, and 22 g of deionized water, mix them evenly, and obtain an antibacterial finishing solution.
[0069] The mass ratio of modified silica-silk fibroin composite solution, modified nano-copper sol and deionized water is 25:2.5:11.
[0070] Step 4: Preparation of non-woven fabric:
[0071] 65 parts of polypropylene and 10 parts of succinoglycan were mixed evenly, dried at 77°C for 1.5 hours, melt-blown at 250°C, with a winding speed of 5 m / min and a receiving distance of the melt-blown fabric of 300 mm to obtain a non-woven fabric;
[0072] Take the non-woven fabric, soak it in deionized water for 35 minutes, wash it, and dry it; take the non-woven fabric and immerse it in antibacterial finishing liquid at 30°C for 23 minutes, roll it on a vertical rolling mill, and dry it at 72°C to obtain a tear-resistant antibacterial non-woven fabric.
[0073] Example 5: No tannic acid is added to modify the silicon dioxide, and the rest is the same as Example 1.
[0074] Step 1: Preparation of modified silica-silk fibroin composite solution:
[0075] Take 100 mL of anhydrous ethanol and 34 mL of ethyl orthosilicate, stir at 27°C for 19 min, add 36 mL of aqueous ammonia, stir for 3 h, and let stand for 24 h to obtain silica gel.
[0076] Take 8 g of silica gel, heat it to 47°C, add 0.7 g of polyhexamethylene guanidine, continue stirring for 4 h, add 6 g of silk fibroin and 2 g of ethylenediaminetetraacetic acid, stir at 28°C for 75 min, ultrasonicate for 75 min, and dry to obtain a modified silica-silk fibroin composite solution.
[0077] Step 2: Preparation of modified nano copper sol:
[0078] Take 0.16g of potassium borohydride and 20ml of deionized water, stir evenly to obtain a potassium borohydride solution; take 0.6g of copper sulfate, add 50mL of deionized water to obtain a copper sulfate solution, add 1.5g of sodium dodecyl sulfate, 2.5g of polyvinyl pyrrolidone, and 2mL of ethylenediamine, stir for 1.5h, heat to 43°C, continue stirring, add potassium borohydride solution, at this time the solution changes from light blue to reddish brown, continue stirring for 4min to obtain a modified nano-copper sol.
[0079] Step 3: Preparation of antibacterial finishing liquid:
[0080] Take 50 g of modified silica-silk fibroin composite solution, 5 g of modified nano copper sol, and 22 g of deionized water, mix them evenly, and obtain an antibacterial finishing solution.
[0081] The mass ratio of modified silica-silk fibroin composite solution, modified nano-copper sol and deionized water is 25:2.5:11.
[0082] Step 4: Preparation of non-woven fabric:
[0083] 65 parts of polypropylene and 10 parts of succinoglycan were mixed evenly, dried at 77°C for 1.5 hours, melt-blown at 250°C, with a winding speed of 5 m / min and a receiving distance of the melt-blown fabric of 300 mm to obtain a non-woven fabric;
[0084] Take the non-woven fabric, soak it in deionized water for 35 minutes, wash it, and dry it; take the non-woven fabric and immerse it in antibacterial finishing liquid at 30°C for 23 minutes, roll it on a vertical rolling mill, and dry it at 72°C to obtain a tear-resistant antibacterial non-woven fabric.
[0085] Example 6: No ethylenediamine is added to modify the nano copper sol, and the rest is the same as Example 1.
[0086] Step 1: Preparation of modified silica-silk fibroin composite solution:
[0087] Take 100 mL of anhydrous ethanol and 34 mL of ethyl orthosilicate, stir at 27 ° C for 19 minutes, add 36 mL of ammonia water, stir for 2.5 hours, adjust the pH value of the solution to 5.5 with 0.1 mol / L hydrochloric acid, add 1 g of tannic acid, continue stirring for 2.5 hours, add 28% concentrated ammonia water, adjust the pH value to 8, and age for 11.5 hours to obtain silica gel;
[0088] Take 8 g of silica gel, heat it to 47°C, add 0.7 g of polyhexamethylene guanidine, continue stirring for 4 h, add 6 g of silk fibroin and 2 g of ethylenediaminetetraacetic acid, stir at 28°C for 75 min, ultrasonicate for 75 min, and dry to obtain a modified silica-silk fibroin composite solution.
[0089] Step 2: Preparation of Nano-Copper Sol:
[0090] Take 0.16g of potassium borohydride and 20ml of deionized water, stir evenly to obtain a potassium borohydride solution; take 0.6g of copper sulfate, add 50mL of deionized water to obtain a copper sulfate solution, add 1.5g of sodium dodecyl sulfate and 2.5g of polyvinyl pyrrolidone, stir for 1.5h, heat to 43°C, continue stirring, add potassium borohydride solution, at this time the solution changes from light blue to reddish brown, continue stirring for 4min to obtain a nano copper sol.
[0091] Step 3: Preparation of antibacterial finishing liquid:
[0092] Take 50 g of modified silica-silk fibroin composite solution, 5 g of nano copper sol, and 22 g of deionized water, mix them evenly, and obtain an antibacterial finishing solution.
[0093] The mass ratio of modified silica-silk fibroin composite solution, nano copper sol and deionized water is 25:2.5:11.
[0094] Step 4: Preparation of non-woven fabric:
[0095] 65 parts of polypropylene and 10 parts of succinoglycan were mixed evenly, dried at 77°C for 1.5 hours, melt-blown at 250°C, with a winding speed of 5 m / min and a receiving distance of the melt-blown fabric of 300 mm to obtain a non-woven fabric;
[0096] Take the non-woven fabric, soak it in deionized water for 35 minutes, wash it, and dry it; take the non-woven fabric and immerse it in antibacterial finishing liquid at 30°C for 23 minutes, roll it on a vertical rolling mill, and dry it at 72°C to obtain a tear-resistant antibacterial non-woven fabric.
[0097] Example 7: The amount of modified nano copper sol added is reduced, and the rest is the same as Example 1.
[0098] Step 1: Preparation of modified silica-silk fibroin composite solution:
[0099] Take 100 mL of anhydrous ethanol and 34 mL of ethyl orthosilicate, stir at 27 ° C for 19 minutes, add 36 mL of ammonia water, stir for 2.5 hours, adjust the pH value of the solution to 5.5 with 0.1 mol / L hydrochloric acid, add 1 g of tannic acid, continue stirring for 2.5 hours, add 28% concentrated ammonia water, adjust the pH value to 8, and age for 11.5 hours to obtain silica gel;
[0100] Take 8 g of silica gel, heat it to 47°C, add 0.7 g of polyhexamethylene guanidine, continue stirring for 4 h, add 6 g of silk fibroin and 2 g of ethylenediaminetetraacetic acid, stir at 28°C for 75 min, ultrasonicate for 75 min, and dry to obtain a modified silica-silk fibroin composite solution.
[0101] Step 2: Preparation of modified nano copper sol:
[0102] Take 0.16g of potassium borohydride and 20ml of deionized water, stir evenly to obtain a potassium borohydride solution; take 0.6g of copper sulfate, add 50mL of deionized water to obtain a copper sulfate solution, add 1.5g of sodium dodecyl sulfate, 2.5g of polyvinyl pyrrolidone, and 2mL of ethylenediamine, stir for 1.5h, heat to 43°C, continue stirring, add potassium borohydride solution, at this time the solution changes from light blue to reddish brown, continue stirring for 4min to obtain a modified nano-copper sol.
[0103] Step 3: Preparation of antibacterial finishing liquid:
[0104] Take 50 g of modified silica-silk fibroin composite solution, 2 g of modified nano copper sol, and 22 g of deionized water, mix them evenly, and obtain an antibacterial finishing solution.
[0105] The mass ratio of the modified silica-silk fibroin composite solution, the modified nano-copper sol and deionized water was controlled to be 25:1:11.
[0106] Step 4: Preparation of non-woven fabric:
[0107] 65 parts of polypropylene and 10 parts of succinoglycan were mixed evenly, dried at 77°C for 1.5 hours, melt-blown at 250°C, with a winding speed of 5 m / min and a receiving distance of the melt-blown fabric of 300 mm to obtain a non-woven fabric;
[0108] Take the non-woven fabric, soak it in deionized water for 35 minutes, wash it, and dry it; take the non-woven fabric and immerse it in antibacterial finishing liquid at 30°C for 23 minutes, roll it on a vertical rolling mill, and dry it at 72°C to obtain a tear-resistant antibacterial non-woven fabric.
[0109] experiment
[0110] The tear-resistant and antibacterial non-woven fabrics prepared in Examples 1 to 7 were tested for performance, and the tear strength of the non-woven fabrics was tested according to FZ-60006-91 "Determination of tear strength of non-woven fabrics". The non-woven fabric was cut into 6 cm × 6 cm square pieces, sterilized at 120 ° C for 30 min, and then placed in a conical flask, 80 mL of liquid culture medium was added, 5 mL of the test bacterial solution was added, constant temperature oscillation was performed at 25 ° C for 18 h, the bacterial solution was taken out, diluted, 1 mL of the diluted bacterial solution was taken out with a pipette and added to the plate, and cultured at 37 for 48 h to test the antibacterial rate.
[0111] The obtained data are shown in the following table:
[0112]
[0113] Conclusion: It can be seen from the data in the table that in Example 4, ethylenediaminetetraacetic acid is not added, the stability of nano-copper is poor, and the antibacterial effect of the non-woven fabric is deteriorated. In Example 5, tannic acid is not added to modify silica, the active sites of silica are reduced, the grafting rate of polyhexamethyleneguanidine is reduced, and the antibacterial effect is weakened. In Example 6, ethylenediamine is not added to modify the nano-copper sol, the dispersibility of nano-copper in the finishing liquid is deteriorated, and the antibacterial effect of the non-woven fabric is deteriorated. In Example 7, the amount of modified nano-copper sol added is reduced, and the antibacterial effect of the non-woven fabric is deteriorated.
[0114] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a tear-resistant antibacterial nonwoven fabric, characterized in that: The following steps are involved: Step 1: taking a modified silica-silk fibroin composite solution, a modified nano copper sol, and deionized water, and mixing them evenly to obtain an antibacterial finishing solution; Step 2: Evenly mix polypropylene and succinoglycan, dry, melt-blown and roll to obtain a non-woven fabric; Step 3: Take the non-woven fabric, soak it in deionized water for 30-40 minutes, wash it, and dry it; take the non-woven fabric and immerse it in the antibacterial finishing liquid at 25-35° C. for 20-25 minutes, roll it, and dry it at 70-75° C. to obtain a tear-resistant antibacterial non-woven fabric; In step 1, the preparation method of the modified silica-silk fibroin composite solution is as follows: taking silica gel, heating to 45-50° C., adding polyhexamethylene guanidine, continuing stirring for 3-5 hours, adding silk fibroin and ethylenediaminetetraacetic acid, stirring at 25-30° C. for 70-80 minutes, ultrasonicating for 70-80 minutes, and drying to obtain a modified silica-silk fibroin composite solution; The preparation method of the silica gel is as follows: taking anhydrous ethanol and ethyl orthosilicate, stirring at 25-28° C. for 18-20 minutes, adding ammonia water, stirring for 2-3 hours, adjusting the pH value of the solution to 5-5.5 with hydrochloric acid, adding tannic acid, continuing to stir for 2-3 hours, adding concentrated ammonia water, adjusting the pH value to 8-8.5, aging for 11-12 hours, and obtaining the silica gel; In step 1, the preparation method of the modified nano copper sol is as follows: potassium borohydride and deionized water are taken, stirred evenly to obtain a potassium borohydride solution; copper sulfate is taken, deionized water is added to obtain a copper sulfate solution, sodium dodecyl sulfate, polyvinyl pyrrolidone, and ethylenediamine are added, stirred for 1-2 hours, heated to 42-45°C, continued to stir, potassium borohydride solution is added, and continued to stir for 3-5 minutes to obtain a modified nano copper sol.
2. The method for preparing a tear-resistant antibacterial nonwoven fabric according to claim 1, characterized in that: In step 1, the mass ratio of the modified silica-silk fibroin composite solution, the modified nano-copper sol, and deionized water is 25:(2-3):(10-12).
3. The method for preparing a tear-resistant antibacterial nonwoven fabric according to claim 1, characterized in that: The nonwoven fabric comprises the following components: 60-70 parts by weight of polypropylene and 8-12 parts by weight of succinoglycan.
4. The method for preparing a tear-resistant antibacterial nonwoven fabric according to claim 1, characterized in that: In step 2, polypropylene and succinoglycan are uniformly mixed, dried at 75-80° C. for 1-2 hours, melt-blown at 240-260° C., and rolled up at a winding speed of (5-10) m / min to obtain a non-woven fabric.
5. A tear-resistant antibacterial non-woven fabric prepared according to the method for preparing a tear-resistant antibacterial non-woven fabric according to any one of claims 1 to 4.